2012
DOI: 10.1016/j.immuni.2012.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Th22 Cells Are an Important Source of IL-22 for Host Protection against Enteropathogenic Bacteria

Abstract: SUMMARY Interleukin-22 (IL-22) is central to host protection against bacterial infections at barrier sites. Both innate lymphoid cells (ILCs) and T cells produce IL-22. However, the specific contributions of CD4+ T cells and their developmental origins are unclear. We found that the enteric pathogen Citrobacter rodentium induced sequential waves of IL-22 producing ILCs and CD4+ T cells that were each critical to host defense during a primary infection. Whereas IL-22 production by ILCs was strictly IL-23–depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
419
1
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(455 citation statements)
references
References 49 publications
31
419
1
4
Order By: Relevance
“…Our results are congruent with recent reports supporting a key function of T cells and the Th17 pathway (including IL-17 family, IL-22, and IL-23 cytokines) in defense against infections at skin and mucocutaneous barriers (59)(60)(61)(62)(63)(64)(65)(66). Corticosteroid inhibition of IL-22 production has been associated with impaired barrier protection and increased bacterial invasion (67).…”
Section: Discussionsupporting
confidence: 92%
“…Our results are congruent with recent reports supporting a key function of T cells and the Th17 pathway (including IL-17 family, IL-22, and IL-23 cytokines) in defense against infections at skin and mucocutaneous barriers (59)(60)(61)(62)(63)(64)(65)(66). Corticosteroid inhibition of IL-22 production has been associated with impaired barrier protection and increased bacterial invasion (67).…”
Section: Discussionsupporting
confidence: 92%
“…We challenged 8‐month‐old mice on eRapa for 6 months with flagel‐lin, which augments IL‐23‐driven IL‐22 from intestinal group 3 ILC (Basu  et al ., 2012). Mice on eRapa experienced eightfold increased flagellin‐driven serum IL‐22 versus Eudragit (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6D). As IL‐22‐producing group 3 ILCs protect from intestinal bacterial infection, we challenged RAG2 −/− mice on eRapa or Eudragit for 1 month with the flagellated bacterium C. rodentium as described (Basu et al ., 2012). eRapa did not protect from chronic infection as determined by survival, weight change, and colon length (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In mammals, IL-22 plays an important role in the development of chronic inflammatory diseases and in preventing tissue damage, acting as a T H -17 cytokine (Zheng et al, 2007;Ma et al, 2008). Recently, it has been found that IL-22 can enhance mucosal barrier function (Basu et al, 2012;Leung and Loke, 2012), and activate antimicrobial defense in host by inducing the expression of antimicrobial peptides (AMPs), such as ␤-defensins 2 and 3 (Liang et al, 2006). IL-22 has been identified in many lower vertebrate species, such as zebrafish (Danio rerio) (Igawa et al, 2006), rainbow trout (Oncorhynchus mykiss) (Monte et al, 2011), and the amphibian Xenopus tropicalis (Qi and Nie, 2008).…”
Section: Introductionmentioning
confidence: 99%